FAKTOR-FAKTOR YANG MEMENGARUHI EARNINGS MANAGEMENT - Nadine Felicia; Frestin Chrisnanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to examine the effect of growth, leverage, fixed asset turnover, profitability, firm size, firm age, audit quality, audit independence, and motivational bonuses. Using 300 years of data from 100 samples of listed manufacturing company in Indonesia Stock Exchange for the period 2018 until 2020 that selected by using purposive sampling method. This study uses multiple regression method. Finding of this study indicate that growth, leverage, profitability, and audit quality have a effect on earnings management. Meanwhile the result of this study then show that fixed asset turnover, firm size, firm age, audit independence, and motivational bonuses do not have a effect on earnings management.